Advances in modeling the Charcot-Marie-Tooth disease: Human induced pluripotent stem cell-derived Schwann cells harboring SH3TC2 variants - Loret, Camille; Scherrer, Camille; Rovini, Amandine; Pyromali, Ioanna; Faye, Pierre-Antoine; Nizou, Angélique; Sturtz, Franck; Favreau, Frédéric; Lia, Anne-Sophie (European journal of cell biology, 2025)
Human induced pluripotent stem cells (hiPSCs) represent a powerful tool for investigating neuropathological disorders, such as Charcot-Marie-Tooth disease (CMT), the most prevalent inherited peripheral neuropathy, where the cells of interest are hardly accessible. Advancing the development of appropriate cellular models is crucial for studying the disease’s pathophysiology. In this study, we present the first two isogenic hiPSC-derived Schwann cell models for studying CMT4C, also known as AR-CMTde-SH3TC2. This subtype of CMT is associated with alterations in SH3TC2 and is the most prevalent form of autosomal recessive demyelinating CMT. We aimed to study the impact of two nonsense mutations in SH3TC2. To achieve this, we used two CRISPR hiPSC clones, one carrying a homozygous nonsense mutation: c.211C>T, p.Gln71*, and the other one, carrying the most common AR-CMTde-SH3TC2 alteration, c.2860G>A, p.Arg954*. To study the endogenous expression of SH3TC2 in the cells mainly altered in AR-CMTde-SH3TC2, we initiated the differentiation of both our CMT clones and their isogenic control into Schwann cells (SCs). This study represents the first in vitro investigation of human endogenous SH3TC2 expression in AR-CMTde-SH3TC2 hiPSC-derived SC models, allowing for the examination of its expression and of its cellular impact. By comparing this AR-CMTde-SH3TC2 models to the control one, we observed disparities in RNA and protein expression of SH3TC2. Additionally, our RNA and coculture experiments with hiPSC-derived motor neurons (MNs) revealed delayed maturation of SCs and a reduced ability of SH3TC2-deficient SCs to sustain motor neuron culture. Our findings also demonstrated a disability in receptor recycling in SH3TC2-deficient cells, depending on the AR-CMTde-SH3TC2 alteration. These hiPSC-derived-SC models further provide a new modelling tool for studying Schwann cell contribution to CMT4C. •Novel isogenic hiPSC-derived Schwann cell models with SH3TC2-c.211C>T-p.Gln71* and SH3TC2-c.2860C>T-p.Arg954* alterations.•Human endogenous SH3TC2 expression studied in control and mutated hiPSC-derived Schwann cells.•SH3TC2-deficient hiPSC-derived Schwann cells show reduced mRNA and protein levels.•SH3TC2-deficient Schwann cells exhibit delayed maturation and impaired support in co-culture with isogenic WT motor neurons.